356 Reporting recurrent and subsequent injuries in professional sport: a systematic review. (3rd March 2020) - Bitchell, Leah; Varley-Campbell, Jo; Robinson, Gemma; Stiles, Victoria; Mathema, Prabhat; Moore, Isabel
Abstract : Background: Traditional injury surveillance in professional sport provides group level analysis of injury risk, categorising injuries as either 'new' or 'recurrent', with recurrent injuries reported as being more severe. To encompass different injury classifications and assess individual injury risk, categorising subsequent injuries has been proposed. Yet, it is not known how often subsequent injury models are used in research. Objective: To assess how recurrent and subsequent injuries are reported within professional sport. Design: Systematic review. Setting: Professional or elite level sport with consensus statements. Main outcome measurements: Three online databases were used to search for articles using injury terms (injuries, injury, recurrent, subsequent) and sport terms (football, rugby, athletics, swimming, diving, water-polo, cricket, tennis, horseracing, professional, elite). The definitions, data collection period, number of participants and the overall and recurrent injury values were extracted. Results: Seventy-four full text articles were identified for review. Sixty-four percent reported the recurrence of injuries, and 47 studies were utilised for data extraction. Only 32 reported the incidence of all injuries and studies varied in reporting recurrent injuries, opting to use either the number of injuries (10%), proportion of all injuries (43%), incidence (5%) or a combination (42%). Seven studies used the subsequent injury terminology, with two of these studies utilising the subsequent injury categorisation model (SIC). The majority of subsequent injuries were categorised as SIC 10 (different body part, unrelated to index injury) with proportions ranging from 51% to 59%. The proportion of recurrent injuries (exact same body area and nature related to index injury) ranged from 5% to 21%. Conclusions: Reporting recurrent or subsequent injuries remains inconsistent within research, and few studies have utilised subsequent injury models. Consequently, there is limited understanding of individual injury risk within professional sport, which may affect the development of individualised injury prevention and rehabilitation strategies.